2021
DOI: 10.48550/arxiv.2106.00389
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Analysis of Vision-based Abnormal Red Blood Cell Classification

Annika Wong,
Nantheera Anantrasirichai,
Thanarat H. Chalidabhongse
et al.

Abstract: Identification of abnormalities in red blood cells (RBC) is key to diagnosing a range of medical conditions from anaemia to liver disease. Currently this is done manually, a time-consuming and subjective process. This paper presents an automated process utilising the advantages of machine learning to increase capacity and standardisation of cell abnormality detection, and its performance is analysed. Three different machine learning technologies were used: a Support Vector Machine (SVM), a classical machine le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…A total of 1000 samples were tested in this experiment, that is, 100 test samples for A comparison of different strategies with the proposed HPKNN classifier is shown in Table 6. The proposed HPKNN (97.86%) outperforms SVM-SOMTE 1 + CSL (76.09%), 33 TabNet-SOMTE 1 + CSL(69.7%), 33 optimizable SVM (97.29%), and optimizable Tree (95.98%) in terms of sensitivity analysis. The proposed HPKNN (97.86%) outperforms SVM-SOMTE 1 + CSL (76.73%), TabNet-SOMTE 1 + CSL (69.56%), and Effi-cientNet (91.04%), 3 optimizable SVM (96.98%), and optimizable Tree (95.87%) in terms of F 1 -score analysis.…”
Section: Robustness Analysis Of the Experimental Datasetsmentioning
confidence: 97%
“…A total of 1000 samples were tested in this experiment, that is, 100 test samples for A comparison of different strategies with the proposed HPKNN classifier is shown in Table 6. The proposed HPKNN (97.86%) outperforms SVM-SOMTE 1 + CSL (76.09%), 33 TabNet-SOMTE 1 + CSL(69.7%), 33 optimizable SVM (97.29%), and optimizable Tree (95.98%) in terms of sensitivity analysis. The proposed HPKNN (97.86%) outperforms SVM-SOMTE 1 + CSL (76.73%), TabNet-SOMTE 1 + CSL (69.56%), and Effi-cientNet (91.04%), 3 optimizable SVM (96.98%), and optimizable Tree (95.87%) in terms of F 1 -score analysis.…”
Section: Robustness Analysis Of the Experimental Datasetsmentioning
confidence: 97%
“…Fortunately, rapid advancements in the field of machine learning have yielded deep convolutional neural network architectures (CNNs) that surpassed all former approaches to image classification tasks [15][16][17][18][19] . Most scientific fields have by now felt the impact of deep learning (DL) enabled image analysis and there have already been several attempts to utilize CNNs for classifying morphology of RBCs in different contexts [20][21][22][23] . Although these previous studies showed varying degrees of success, each approach has been tailored to a specific imaging modality, and the common lack of dataset and code accessibility made it impossible to compare the approaches.…”
mentioning
confidence: 99%
“…The average precisions are 90.25%, 80.41%, and 98.92% for platelets, RBCs, and WBCs respectively. (Wong et al, 2021) proposed RBC classification with 3 methods. Our dataset also was used in this work.…”
Section: Previous Studiesmentioning
confidence: 99%
“…The number near each cell shows the number of predicted RBC types. The number is in (Wong et al, 2021) reported the results of using SVM and TabNet to classify the RBCs into 11 classes on the same dataset as used in this paper. They employed the SMOTE technique with cost-sensitive learning to handle the imbalanced dataset.…”
Section: Rbc Classificationmentioning
confidence: 99%
See 1 more Smart Citation